Follow-Up Study to Family Members’ Reactions to the Initial Special Education Meeting - Ingalls, Lawrence; Hammond, Helen; Paez, Carlos; Rodriguez, Ivan (Journal of the American Academy of Special Education Professionals, 2016)
Family involvement is a central component of Individuals with Disabilities Education Act (IDEA). Family members are to be integrated in all aspects of the special education process. At the onset, of family involvement, it is imperative for educators to be aware of possible reactions family members may experience in this initial stage. This follow-up study examined family members’ reactions from their initial introduction into the special education system. Interviews with 281 family members over a five-year span provided supportive results of a previous study examining family members’ reactions. In this study, the researchers also report on detailed suggestions from the family members on ways to improve their initial involvement were additionally compiled in this study.